2015
DOI: 10.1016/j.rppnen.2014.02.004
|View full text |Cite
|
Sign up to set email alerts
|

The overall impact of COPD (CAT) and BODE index on COPD male patients: correlation?

Abstract: As pre-existent data in the literature (exacerbations and benefit of rehabilitation in COPD), the positive correlations found with BODE index reinforce the discriminative validity of CAT as a complement in the evaluation of what the true impact of COPD is on a patient's daily life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Our study showed that statistically significant correlation among CAT, CCQ, and BODE INDEX scores in assessing the disease stage in stable patients of COPD; very well in consistence with various previous studies. [ 14 15 ] These scores also correlate well statistically with FeV1% predicted; the basic parameter for an individual in the study sample for assessing the particular severity stage of COPD (using GOLD parameters). Large-scale longitudinal prospective studies are required to further elaborate the results.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Our study showed that statistically significant correlation among CAT, CCQ, and BODE INDEX scores in assessing the disease stage in stable patients of COPD; very well in consistence with various previous studies. [ 14 15 ] These scores also correlate well statistically with FeV1% predicted; the basic parameter for an individual in the study sample for assessing the particular severity stage of COPD (using GOLD parameters). Large-scale longitudinal prospective studies are required to further elaborate the results.…”
Section: Discussionmentioning
confidence: 70%
“…They found that the total CCQ score correlated well with BODE score ( P < 0.001) and GOLD staging ( P < 0.001). In an another retrospective study including 50 patients conducted by Ladeira et al .,[ 15 ] CAT score and its impact on a patient's daily life (assessed with mMRC, 6MWT) were correlated with BODE index score: r = 0.475, P < 0.01, and r = 0.377, P = 0.004, and BODE index class: r = 0.357, P = 0.011, and r = 0.326, P = 0.021.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Moreover, numerous studies have observed that the CAT score is associated with COPD severity and risk of exacerbation. 22 25 …”
Section: Introductionmentioning
confidence: 99%
“…1 La EPOC es actualmente la tercera causa de muerte y será la quinta causa de discapacidad para 2030 a nivel internacional. 2 Los costos en salud de la EPOC son cuantiosos, 3 pero las estimaciones suelen provenir de países de ingresos altos [4][5][6][7][8][9][10][11] y se han descrito para países como Estados Unidos, Inglaterra, España, Rumania y Colombia. [12][13][14][15][16][17][18][19][20] *.…”
Section: Introductionunclassified